Inventory of the Historical Heritage Site of Kedatukan Urung Sapuluh Dua Kuta in Hamparan Perak, Deli Serdang Regency - Putri, Annisa Sylvia; Ali, M Nasihudin (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research aims to find out historical heritage sites in Hamparan Perak District, and increase insight and understanding for the younger generation so that they know more about the local history of North Sumatra and increase awareness of the local community and government regarding the Kedatukan heritage site in Silver Overlay. This research uses qualitative methods, which focus on in-depth observations by interviewing sources, as well as conducting observations in the field and also using some documentation. Hamparan Perak Subdistrict, Deli Serdang Regency, was previously one of the main areas of Kedatukan Urung Sapuluh Dua Kuta and has left behind many historical relics. The results of research found by researchers are in the form of relics during the reign of Kedatukan Urung Sapuluh Dua Kuta, namely in the form of Mosques, Palace Houses, Tombs and Manuscripts.